2016
DOI: 10.3390/w8030103
|View full text |Cite
|
Sign up to set email alerts
|

The Water Abstraction License Regime in Italy: A Case for Reform?

Abstract: Abstract:The current Water Abstraction License (WAL) regime in Italy is no longer flexible enough to cope with the challenges posed by human-induced climate and global environmental changes. The cornerstones of the current regime were laid down in the 1930s and have remained essentially unchanged ever since. The sole noteworthy reform of the Italian WAL regime was the decentralization of the regulatory competences from the state to the regional authorities in the late 1990s. In this paper, we review the WAL re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Climate models predict an exacerbation of their torrential characteristics, with an intensification of extreme meteorological phenomena and reduced flow rates in the summer season [9]. This situation is further aggravated by increases in water withdrawals for irrigation purposes [25,26]. The Tiber River basin (Central Italy) is characterized by the presence of a large number of endemic fish species with limited areal distribution which are, therefore, highly vulnerable to extinction [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Climate models predict an exacerbation of their torrential characteristics, with an intensification of extreme meteorological phenomena and reduced flow rates in the summer season [9]. This situation is further aggravated by increases in water withdrawals for irrigation purposes [25,26]. The Tiber River basin (Central Italy) is characterized by the presence of a large number of endemic fish species with limited areal distribution which are, therefore, highly vulnerable to extinction [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…6 A variety of programmes are contained within the National Rural Network to achieve these goals. For more information, see (RRN, 2020 [94]). 7 OECD calculations based on EAFRD data.…”
Section: Governance Framework Affecting Disaster Risk Management In Agriculturementioning
confidence: 99%
“…Data on water abstractions are often very sparse and inconsistent. Ziolkowska and Ziolkowski [38,39] showed that in many European countries, there is still a deep lack of information and data; specifically, agricultural water use data in southern Europe is very problematic due to a lack of updated information, making any estimate of this critical issue very difficult [40].…”
Section: Water Abstractions Evaluationmentioning
confidence: 99%